Educational Innovation in Economics and Business
XXIV, 282 p.
Keywords: Many workplaces have become characterized as learning organizations where knowledge workers provide the required competitive edge. Due to the dynamic changes in the economic structures, adaptive, generative, lifelong, and continuous learning have become norms. Leaders in the corporate world have a greater responsibility to provide direction in knowledge building and knowledge delivery systems. The key competencies required for leadership have been impacted by the change in corporate structures and the ever-changing formats that define competitive business landscapes. Traditional universities are also experiencing greater demand to provide the necessary skill sets required by individuals tasked with developing, incorporating, and communicating new knowledge. When it comes to learning models, the business focus on "continuous improvement" makes all the sense in the world. It is in this spirit of continuous learning that this book was compiled. The seventh volume in the series Educational Innovation in Economics and Business contains a unique selection of articles addressing four major themes: (I) Designing New Education Models, (II) Preparing Students for Work in the Corporate Arena, (III) Using Technology to Enhance Learning Environments, and (IV) Methods to Maximize Student Learning. It is meant for educators in corporate training centers as well as for teachers in further and higher education.